SISTEM AKUNTANSI PENGGAJIAN DAN PENGENDALIAN INTERNAL PEGAWAI NEGERI SIPIL PADA KEMENTERIAN PEKERJAAN UMUM DAN PERUMAHAN RAKYAT - Delfy Yandri; Ayu Fitri Rosianie (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2021)
Giving salaries to employees should be the prime attention of the leadership. The provision of adequate salaries will have a positive influence on employee morale. Salary is a substitute for the contribution of labor and expertise that has been given by employees to the company. However, the salary for civil servants has been regulated in the law based on class. The payroll and wage accounting system is designed to handle transactions for calculating employee salaries and wages and their payments. This system consists of a network of procedures, including procedures for recording attendance and working time, procedures for making lists of salaries and wages, procedures for paying salaries and wages, and procedures for distributing salaries and wages. Activation of government agencies in the payroll system is going well, so it is appropriate for these government agencies to implement a correct payroll system and integration of various related functions so that it is expected to overcome the risk of fraud and fraud in the payroll system